The Use of Hybrid Contract in the Innovation of Islamic Banking Product - Nun Harrieti (Hasanuddin Law Review, 2018)
ASEAN Banking Integration Framework (ABIF) provides market access and operational flexibility for Quality ASEAN Banks (QAB) in ASEAN countries. Indonesian sharia banking is faced with various challenges in fulfilling QAB qualification within this ABIF framework, one of which is the need for product innovations that can meet the needs of community transactions. One of the innovation is through hybrid contract. This study aims to analyze the validity of the use of contract hybrid in the innovation of Sharia banking products in order to encounter ABIF including its legal consequences under the prevailing laws and regulations in Indonesia. This paper was a normative juridical research with analytical descriptive approach. The validity of the use of hybrid contract in the innovation of Islamic banking products in Indonesia in order to encounter ABIF is based on the provisions of the DSN-MUI Fatwa which regulates the covenants used in the innovation of Islamic banking products, so that sharia banking that will make product innovation in Indonesia must ask Fatwa on the terms of contract which will be used in product innovation. The legal consequences of hybrid contract in the innovation of sharia banking products in Indonesia in order to face ABIF are subject to the provisions of Financial Services Authority Regulation (POJK) of Products and Activities of Sharia Banks and Sharia Business Units, so banks are required to apply the Sharia Principles in issuing their product innovation supported by the National Sharia Council Fatwa of the Indonesian Ulama Council which become the basis for the issuance of product innovation and accompanied by the Sharia Supervisory Board's opinion on the Product's innovation.